bài 1:Cho M=(1+$\frac{a}{a^{2}+1}$) :($\frac{a}{a^{2}-1}$-$\frac{2a}{a^{3}-a^{2}+a-1}$ ) a)tìm điều kiện xác định b)rút gọn M bài 2:cho f(x)=2$x^{2}$

Question

bài 1:Cho M=(1+$\frac{a}{a^{2}+1}$) :($\frac{a}{a^{2}-1}$-$\frac{2a}{a^{3}-a^{2}+a-1}$ )
a)tìm điều kiện xác định
b)rút gọn M
bài 2:cho f(x)=2$x^{2}$+ax+1 và g(x)=x-3
tìm a để f(x):g(x) dư 4

in progress 0
Ivy 1 tháng 2021-08-11T04:42:16+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-11T04:43:21+00:00

    Giải thích các bước giải:

    Bài 1:

    a)đkxđk : $a-1\ne 0$

    b)$M=(1+\dfrac{a}{a^2+1}):(\dfrac{1}{a-1}-\dfrac{2a}{a^3-a^2+a-1})$ 

    $\to M=\dfrac{a^2+1+a}{a^2+1}:(\dfrac{1}{a-1}-\dfrac{2a}{(a-1)(a^2+1)})$ 

    $\to M=\dfrac{a^2+1+a}{a^2+1}:\dfrac{a^2+1-2a}{(a-1)(a^2+1)}$ 

    $\to M=\dfrac{a^2+1+a}{a^2+1}:\dfrac{(a-1)^2}{(a-1)(a^2+1)}$ 

    $\to M=\dfrac{a^2+a+1}{a^2+1}:\dfrac{a-1}{a^2+1}$ 

    $\to M=\dfrac{a^2+a+1}{a^2+1}.\dfrac{a^2+1}{a-1}$ 

    $\to M=\dfrac{a^2+a+1}{a-1}$ 

    c.Để $M\in Z\to a^2+a+1\quad\vdots\quad a-1$

    $\to a^2-1+a-1+3\quad\vdots\quad a-1$

    $\to (a-1)(a+1)+(a-1)+3\quad\vdots\quad a-1$

    $\to 3\quad\vdots\quad a-1$

    $\to a-1\in\{1,3,-1,-3\}\to a\in\{2,4,0,-2\}$

    Bài 2 :

    Để $f(x)$ chia $g(x)$ dư 4

    $\to f(3)+4=0\to 2.3^2+3a+1+4=0\to a=\dfrac{-23}3$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )